STUDI EVALUASI PELAKSANAAN PENDIDIKAN BUDI PEKERTI DALAM IMPLEMENTASI KTSP DI SMP NEGERI KABUPATEN GIANYAR - Hery Nugroho; Ni Ketut Suriati (Jurnal Visipena, 2019)
This research aims to obtain: (1) the description or description about the effectiveness of the implementation of the educational Character of the context of Gianyar in junior high, (2) the description or description about the effectiveness of the implementation of the education of minds. Pekerti reviewed from inp-utdi Junior Gianyar Regency, (3) the description or description about the effectiveness of the implementation of the education process in terms of Manners in the Junior High School of Gianyar Regency, and (4). A picture or a description of the effectiveness of the implementation of the educational Character of prduk Junior High School in Gianyar Regency. This research includes the type of evaluative research by adopting the model of evaluation of CIPP. Context variables measured with instruments in the form of a questionnaire context, input variables are measured with instruments in the form of questionnaire input, and process variables measured with instruments in the form of the questionnaire process, variable product is measured by instruments in the form of a questionnaire product. Sample research totalling 9 27 principal, teacher, and Junior High School students in the country 369 Gianyar Regency is drawn using random sampling techniques. The data in the form of a score variable context, the score variable inputs, and product and process variables score further analyzed with the road changed the score to a t-score. The results showed that: (1) education, implementation of Manners is effective in terms of the context of Gianyar in junior high (2) implementation of Character education is not effective in terms of input in Gianyar Junior 3) implementation of Character education is not effective in terms of the process of Gianyar in junior high, (4) the implementation of Character education is effective in terms of the process of Gianyar, in junior high. (5) educational implementation constraints manners is not terakomodasinya the value of the character that develops in the community. Once interpreted in a quadrant of the effectiveness criteria Glickman, the effectiveness of the implementation of Character education are included in the quadrant less effective. Thus it can be concluded that the SMP Negeri Gianyar Regency less effectively implement character education in terms of context, input, process and product. Abstrak Penelitian ini bertujuan untuk memperoleh: (1) gambaran atau deskripsi tentang efektivitas pelaksanaan pendidikan Budi Pekerti ditinjau dari konteks di SMP Kabupaten Gianyar, (2). gambaran atau deskripsi tentang efektivitas pelaksanaan pendidikan Budi Pekerti ditinjau dari inp-utdi SMP Kabupaten Gianyar,(3) gambaran atau deskripsi tentang efektivitas pelaksanaan pendidikan Budi Pekerti ditinjau dari proses di SMP Kabupaten Gianyar,dan (4). Gambaran atau deskripsi tentang efektivitas pelaksanaan pendidikan Budi Pekerti ditinjau dari prduk di SMP Kabupaten Gianyar. Penelitian ini termasuk jenis penelitian evaluatif dengan mengadopsi model evaluasi CIPP. Variabel konteks diukur dengan instrumen berupa kuesioner konteks, variabel input diukur dengan instrumen berupa kuesioner input, dan variabel proses diukur dengan instrumen berupa kuesioner proses, Variabel produk diukur dengan instrumen berupa kuesioner produk. Sampel penelitian berjumlah 9 Kepala sekolah, 27 guru , dan 369 siswa pada SMP Negeri Kabupaten Gianyar yang diambil dengan menggunakan teknik pengambilan sampel secara random. Data yang berupa skor variabel konteks, skor variabel input, dan skor variabel proses dan produk selanjutnya dianalisis dengan jalan mengubah skor tersebut ke skor-t. Hasil penelitian menunjukkan bahwa: (1), pelaksanaan pendidikan Budi Pekerti adalah efektif ditinjau dari konteks di SMP Kabupaten Gianyar (2) pelaksanaan pendidikan Budi Pekerti adalah tidak efektif ditinjau dari input di SMP Kabupaten Gianyar 3) pelaksanaan pendidikan Budi Pekerti adalah tidak efektif ditinjau dari proses di SMP Kabupaten Gianyar, (4) pelaksanaan pendidikan Budi Pekerti adalah efektif ditinjau dari proses di SMP Kabupaten Gianyar, . (5) kendala pengimplementasian pendidikan budi pekerti adalah tidak terakomodasinya nilai budi pekerti yang berkembang di masyarakat. Setelah diinterpretasikan dalam criteria efektivitas kuadran Glickman, efektivitas pelaksanaan pendidikan Budi Pekerti termasuk dalam kuadran kurang efektif. Dengan demikian dapat disimpulkan bahwa SMP Negeri Kabupaten Gianyar kurang efektif melaksanakan pendidikan budi pekerti ditinjau dari segi konteks, input, proses dan produk. Kata Kunci: Studi Evaluasi, Pendidikan Budi Pekerti, Konteks, Input, Proses, Produk